1990
DOI: 10.1185/03007999009111650
|View full text |Cite
|
Sign up to set email alerts
|

Etizolam in the treatment of generalized anxiety disorder: a double-blind study versus placebo

Abstract: A double-blind, placebo-controlled study was carried out in 36 patients diagnosed as suffering from Generalized Anxiety Disorder with associated depressive symptoms to assess the efficacy and tolerability of two unitary doses of etizolam. After a 1-week wash-out period on placebo, patients were assigned at random to receive 1 tablet twice daily of either 0.50 mg or 0.25 mg etizolam or placebo for 5 weeks. Assessments were made at entry, on Day 21 and Day 35 of the patients' condition and symptoms using a batte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…One study reported that somatic symptoms were more responsive to diazepam treatment than psychic symptoms, whereas the latter responded more to imipramine [Rickels et al, 1993]. The preferential action of diazepam on the somatic symptoms compared with that on psychic symptoms of anxiety was also shown by a number of studies [Fontaine et al, 1983;Pecknold et al, 1989;Pourmotabbed et al, 1996;Rickels et al, 1982Rickels et al, , 1983, although not all benzodiazepines have been shown to possess this selectivity [Casacchia et al, 1990;Feighner et al, 1983]. In comparison, buspirone is believed to act primarily on symptoms associated with cognitive and interpersonal problems [Rickels et al, 1982], although reports of its specificity are contradictory [Feighner and Cohn, 1989;Pecknold et al, 1989].…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that somatic symptoms were more responsive to diazepam treatment than psychic symptoms, whereas the latter responded more to imipramine [Rickels et al, 1993]. The preferential action of diazepam on the somatic symptoms compared with that on psychic symptoms of anxiety was also shown by a number of studies [Fontaine et al, 1983;Pecknold et al, 1989;Pourmotabbed et al, 1996;Rickels et al, 1982Rickels et al, , 1983, although not all benzodiazepines have been shown to possess this selectivity [Casacchia et al, 1990;Feighner et al, 1983]. In comparison, buspirone is believed to act primarily on symptoms associated with cognitive and interpersonal problems [Rickels et al, 1982], although reports of its specificity are contradictory [Feighner and Cohn, 1989;Pecknold et al, 1989].…”
Section: Discussionmentioning
confidence: 99%
“…Small early clinical trials suggest that etizolam has equivalent anxiolytic effects to alprazolam and bromazepam, with increasing anxiolytic effects seen over the 4 weeks of treatment . Several small trials also suggest improvement in depressive symptoms in addition to anxiety symptoms .…”
Section: Introductionmentioning
confidence: 99%
“…etizolam) (Figure F). They differ in structure by the replacement of a benzene ring with a thiophene ring but they have similar anticonvulsant, anxiolytic and sedative properties . Thienotriazolodiazepines (Figure G) (e.g.…”
Section: The Rise Of the Nps‐benzodiazepinesmentioning
confidence: 99%
“…They differ in structure by the replacement of a benzene ring with a thiophene ring but they have similar anticonvulsant, anxiolytic and sedative properties. [52][53][54] Thienotriazolodiazepines ( Figure 2G) (e.g. brotizolam 54 ) have a triazole ring fused to the diazepine ring, much like the triazolobenzodiazepines.…”
Section: The Rise Of the Nps-benzodiazepinesmentioning
confidence: 99%